Diabetes Mellitus Detection System In Human Body Through Urine Media Using Naïve Bayes Method - Kasmien Adha, Yuda; Erlina, Tati (CHIPSET, 2025)
In Indonesian the level of diabetes mellitus in the community is very high but public awareness is very low due to many of the people WHO are phobic about blood and needles. From the above problems obtained an alternative solution by using urine as a medium to detect diabetes mellitus in a person. The tool made consists of TCS3200 color sensor, MQ-135 gas sensor, Arduino Uno microcontroller, and 16x2 LCD. The system is made using the NaÏve Bayes algorithm to be able to classify urine that has been tested Benedict including into non-diabetes or diabetes, the system is also made using multiple linear regression algorithms to be able to predict the sugar content contained in urine. In this system, the TCS3200 color sensor as an RGB color code reader and the MQ-135 gas sensor as a reading of ammonia gas levels in urine. This system can provide information about the status of urine and how much sugar levels in the body.